EWES AND GOATS' CONTRIBUTION TO THE EU-28 MILK PRODUCTION IN THE PERIOD 2010-2018 - Agatha POPESCU; Cristina TINDECHE; Adelaida HONTUS; Alina MARCUTA; Liviu MARCUTA; Carmen ANGELESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed the trends and relationships in the EU ewes and goats livestock and milk output in the period 2010-2018 based on Eurostat Data using the fixed basis index, descriptive statistics, average yearly growth rate, Bravais- Pearson correlation coefficients, determination coefficient and regression models. The results attested the important contribution given by the two species to the EU milk sector in order to diversify cheese varieties and stimulate consumption and export. While sheep livestock declined in general, and the goats population increased, ewes and goats' milk delivered to dairy industry increased. In the decreasing order, the main EU countries raising sheep are Spain, Romania, Greece, Italy and France, and the main countries growing goats are Greece, Spain, Romania, France, Italy and Netherlands. Raw milk production increased in case of the both species in many countries. Ewe milk is mainly produced in Greece, Spain, Italy and France, while goat milk is especially produced in France, Spain, Netherlands and Greece. The diverse policies, management and marketing and production performance from a country to another pointed out the need to improve farmers skills in resources, livestock and production management, to encourage them to join in associations to benefit of low-price inputs and a direct access to market. The coupled aids financed by the EU are incentives to sustain sheep and goat farming and dairy sector, farmers' income, the valorization of the natural resources, the development of the disadvantaged rural and periurban areas, animal health and welfare, environment quality and biodiversity, and the offer of organic dairy products to consumers.